Dollar a Day Revisited - Ravallion, Martin (World Bank, 2012)
The article presents the first major update of the international $1 a day poverty line, proposed in World Development Report 1990: Poverty for measuring absolute poverty by the standards of the world's poorest countries. In a new and more representative data set of national poverty lines, a marked economic gradient emerges only when consumption per person is above about $2.00 a day at 2005 purchasing power parity. Below this, the average poverty line is $1.25, which is proposed as the new international poverty line. The article tests the robustness of this line to alternative estimation methods and explains how it differs from the old $1 a day line.